2012
DOI: 10.3350/kjhep.2012.18.1.75
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of adefovir and entecavir combination therapy in patients with nucleoside-refractory hepatitis B

Abstract: Background/AimsNewly developed and potent antiviral agents suffer from the problem of drug resistance. Multidrug resistance is a major impediment in the treatment of patients with chronic hepatitis B (CHB). In line with American Association for the Study of Liver Diseases guidelines, adefovir dipivoxil (ADV) add-on therapy is recommended in the case of lamivudine resistance, while tenofovir disoproxil fumarate (TDF) is recommended for ADV or entecavir (ETV) resistance. TDF is currently not available in Korea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Though LAM + ADV has been widely used for rescue therapy in past years for those patients [5,13], patients with sequential LAM and ADV resistance had resistant mutations on the same HBV genome, which anticipated that the combination therapy of LAM + ADV might be unsatisfactory for the CHB patients with genotypic resistance associated with sequential LAM and ADV treatment. Indeed, recent data also showed that the combination therapy of LAM + ADV was not effective and was inferior to ETV containing treatment in suppressing HBV DNA [14], which indicated that ETV based combination therapy would be more superior to the LAM + ADV combination therapy in management of LAM- or ADV- resistant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Though LAM + ADV has been widely used for rescue therapy in past years for those patients [5,13], patients with sequential LAM and ADV resistance had resistant mutations on the same HBV genome, which anticipated that the combination therapy of LAM + ADV might be unsatisfactory for the CHB patients with genotypic resistance associated with sequential LAM and ADV treatment. Indeed, recent data also showed that the combination therapy of LAM + ADV was not effective and was inferior to ETV containing treatment in suppressing HBV DNA [14], which indicated that ETV based combination therapy would be more superior to the LAM + ADV combination therapy in management of LAM- or ADV- resistant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, modification of the treatment strategy may be required in the absence of EVR. Another ADV combination, such as ADV plus ETV, could be an alternative therapy [24,25,26], but the cost will be increased. In addition, the efficacy of ADV plus ETV needs to be demonstrated compared with that of the ADV plus LMV combination because a previous retrospective study failed to show its benefit [27].…”
Section: Discussionmentioning
confidence: 99%
“…The continued use of LAM does not provide any additional antiviral suppression but has been shown to delay the emergence of ADV resistance compared with switching to ADV alone . Nevertheless, resistance to both ADV and LAM can eventually develop during ADV + LAM treatment, and a substantial number of LAM‐experienced patients will have a suboptimal response to ADV + LAM . For TDF, evidence on its clinical efficacy in this patient population has been mainly provided from cohort and case–control studies, with the number of LAM‐resistant patients in TDF registrational trials too small to establish its efficacy in this subgroup, and results from one randomized controlled trial in LAM‐resistant HBV only recently being reported .…”
Section: Introductionmentioning
confidence: 99%